Pressure-Corrected Carotid Stiffness and Young's Modulus: Evaluation in an Outpatient Clinic Setting. (9th February 2021) - van der Bruggen, Myrthe; Spronck, Bart; Bos, Siske; Heusinkveld, Maarten H G; Taddei, Stefano; Ghiadoni, Lorenzo; Delhaas, Tammo; Bruno, Rosa Maria; Reesink, Koen D
Abstract: Background: Conventional measures for assessing arterial stiffness are inherently pressure dependent. Whereas statistical pressure adjustment is feasible in (larger) populations, it is unsuited for the evaluation of an individual patient. Moreover, statistical "correction" for blood pressure may actually correct for: (i) the acute dependence of arterial stiffness on blood pressure at the time of measurement; and/or (ii) the remodeling effect that blood pressure (hypertension) may have on arterial stiffness, but it cannot distinguish between these processes. METHODS: We derived—assuming a single-exponential pressure–diameter relationship—3 theoretically pressure-independent carotid stiffness measures suited for individual patient evaluation: (i) stiffness index β 0, (ii) pressure-corrected carotid pulse wave velocity (cPWVcorr ), and (iii) pressure-corrected Young's modulus ( E corr ). Using linear regression analysis, we evaluated in a sample of the CATOD study cohort changes in mean arterial pressure (ΔMAP) and comparatively the changes in the novel (Δ β 0, ΔcPWVcorr, and Δ E corr ) as well as conventional (ΔcPWV and Δ E ) stiffness measures after a 2.9 ± 1.0-year follow-up. RESULTS: We found no association between ΔMAP and Δ β 0, ΔcPWVcorr, or Δ E corr . In contrast, we did find a significant association between ΔMAP and conventional measures ΔcPWV and Δ E . Additional adjustments for biomechanical confounders and traditional risk factors did neither materially change these associations nor the lack thereof. Conclusions: Our newly proposed pressure-independent carotid stiffness measures avoid the need for statistical correction. Hence, these measures ( β 0, cPWVcorr, and E corr ) can be used in a clinical setting for (i) patient-specific risk assessment and (ii) investigation of potential remodeling effects of (changes in) blood pressure on intrinsic arterial stiffness. Graphical Abstract: